2023
DOI: 10.1002/mds.29398
|View full text |Cite
|
Sign up to set email alerts
|

Double‐Edged Effects of Venglustat on Behavior and Pathology in Mice Overexpressing α‐Synuclein

Abstract: A BS TRACT: Background: Venglustat is a brain-penetrant, small molecule inhibitor of glucosylceramide synthase used in clinical testing for treatment of Parkinson's disease (PD). Despite beneficial effects in certain cellular and rodent models, patients with PD with mutations in GBA, the gene for lysosomal glucocerebrosidase, experienced worsening of their motor function under venglustat treatment (NCT02906020, MOVES-PD, phase 2 trial). Objective: The objective of this study was to evaluate venglustat in mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The efficacy of a low dose of venglustat in our study is likely due to the relatively modest accumulation of gangliosides observed in the Spg11 -/- model. The use of a low dose of venglustat may also avoid or decrease potential adverse effects that were observed in another study in mice (Schidlitzki et al, 2023): a dose of 60 mg/kg/day led to worsening of motor performance, suggesting possible adverse or off-target effects of the molecule (Schidlitzki et al, 2023). The behavioral benefit provided by venglustat treatment was weaker than the one provided by downregulation of St3gal5 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The efficacy of a low dose of venglustat in our study is likely due to the relatively modest accumulation of gangliosides observed in the Spg11 -/- model. The use of a low dose of venglustat may also avoid or decrease potential adverse effects that were observed in another study in mice (Schidlitzki et al, 2023): a dose of 60 mg/kg/day led to worsening of motor performance, suggesting possible adverse or off-target effects of the molecule (Schidlitzki et al, 2023). The behavioral benefit provided by venglustat treatment was weaker than the one provided by downregulation of St3gal5 .…”
Section: Discussionmentioning
confidence: 97%
“…The small molecule venglustat that inhibits an enzyme upstream of St3gal5 also slowed down disease progression, suggesting that targeting the biosynthetic pathway of gangliosides is an effective therapeutic option for SPG11. Venglustat is an inhibitor of glucosylceramide synthase that crosses the blood brain barrier and that has proven to delay the onset of symptoms in mouse models of Sandhoff disease, neuronopathic Gaucher disease, as well as glucocerebrosidase (GBA)-related synucleinopathies (Marshall et al, 2019, 2016; Schidlitzki et al, 2023; Viel et al, 2021). Clinical data suggested safety of the molecule in healthy volunteers as well as Parkinson’s disease and Fabry disease patients (Deegan et al, 2023; Peterschmitt et al, 2022, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, allosteric GCase chaperones would be expected to be less efficient and only effective over longer timescales. The hypothesis would also suggest that GlcCer synthesis is unlikely to be a successful strategy in Parkinson’s disease as further decreases in cytosolic glycolipids could potentially lead to exacerbation of defective vesicle pH (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial was performed for substrate reduction therapy of GBA-PD patients using venglustat to inhibit GlcCer synthesis and reduce lysosomal storage. However, this trial was unsuccessful as treatment was associated with the acceleration of PD symptoms (16,17). This result suggests that GlcCer storage does not cause PD symptoms and is instead necessary for appropriate dopaminergic function.…”
Section: Introductionmentioning
confidence: 99%
“…Venglustat (other names: ibiglustat, GZ/SAR402671) is a brain-penetrant glucosylceramide synthase inhibitor that reduces the production of GCase substrates, glycosphingolipids. Despite good safety and tolerability in a phase I trial with reduction in glucosylceramide levels up to 75%, phase II study revealed that venglustat treatment deteriorates motor function in participants (NCT02906020) [ 256 ]. Having said that, a related small-molecule compound, GZ667161, presented activity towards mutant GCase with no adverse events in vivo [ 257 ].…”
Section: Drugs Targeting α-Synucleinmentioning
confidence: 99%